Individual and relational dynamics perceived to influence the sexual behaviour of adolescents in Ethiopia: a qualitative study - Baraki, Semere Gebremariam; Thupayagale-tshweneagae, Gloria (Frontiers in Reproductive Health, 2024)
BackgroundThere are 1.2 billion adolescents in the world today, more than ever before, making up 16% of the world's population and nearly one-fourth of the total population in Sub-Saharan Africa. Adolescents are facing life-threatening health challenges attributed to sexual and reproductive health issues such as unwanted pregnancies, unsafe abortions, and sexually transmitted infections, including the human immunodeficiency virus, and acquired immunodeficiency syndrome. The aim of this research is to explore the individual and relational levels of factors that drive adolescents to engage in risky sexual behaviour.MethodsA qualitative phenomenological study design was used from February to June 2020. Adolescents and health professionals were selected purposefully. A total of 12 individual in-depth interviews, five focus group discussions with adolescents, and eight key informant interviews with health professionals were conducted using a semi-structured guide. Data analysis was performed using thematic analysis with ATLAS Ti version 7 software. Credibility, dependability, transferability, and confirmability were used to ensure the trustworthiness of the data.ResultsIn this study, two themes were identified; individual level factors such as sexual desire and emotion driven sex, limited knowledge of sexual and reproductive health, and a permissive attitude towards sexual activities drive adolescents to engage in risky sexual behaviour; and relational level factors such as, limited family support and involvement, negative peer pressure and influence, male partner dominance during the partnership, and pressuring females to engage in sexual intercourse were perceived factors influencing adolescents to engage in risky sexual behaviour.ConclusionVarious individual-level and relational-level factors are influencing adolescents to engage in risky sexual behaviour. Socially and culturally acceptable, comprehensive sexual education should be provided for in-school and out-school adolescents to enhance their knowledge, attitude, and skill about sexual and reproductive health. Interventions at the peer and partner level should be considered to enhance the life skills that enable them to resist pressure from peers and their partners. Child-parent communication on sexual and reproductive health matters should be promoted.